p-Methoxyphenol: A potent and effective scavenger for solid-phase peptide synthesis (2020)
During the final step of t-Boc/Bzl, solid-phase peptide synthesis (SPPS)-protecting groups from amino acids (aa) side chains must be removed from the target peptides during cleavage from the solid support. These reaction steps involve hydrolysis with hydrogen fluoride (HF) in the presence of a nucleophile (scavenger), whose function is to trap the carbocations produced during SN1-type reactions. Five peptide sequences were synthesised for evaluating p-methoxyphenol effectiveness as a potent scavenger. After the synthesis, the resin–peptide was then separated into two equal parts to be cleaved using two scavengers: conventional reactive p-cresol (reported in the literature as an effective acyl ion eliminator) and p-methoxyphenol (hypothesised as fulfilling the same functions as the routinely used scavenger). Detailed analysis of the electrostatic potential map (EPM) revealed similarities between these two nucleophiles, regarding net atomic charge, electron density distribution, and similar pKa values. Good scavenger efficacy was observed by chromatography and mass spectrometry results for the synthesised molecules, which revealed that p-methoxyphenol can be used as a potent scavenger during SPPS by t-Boc/Bzl strategy, as similar results were obtained using the conventional scavenger. © 2020 European Peptide Society and John Wiley and Sons, Ltd.